SOAP in a mobile Environment - Dolan, Liam (Trinity College Dublin. Department of Computer Science, 2004)
Recent years has seen a dramatic rise in the number of mobile devices in use. These devices include PDAs, mobile phones and embedded devices such as those found in cars for satellite tracking. As the use of these devices increases so do the expectations of what functionality is offered by the devices. Customers now demand to be able to access the web and check their emails while on the move and in possession of a mobile device. However computing in a wireless environment must overcome many obstacles, such as variable bandwidth and unreliable network connectivity, which are not present in a wired environment.

Middleware is a term used to describe the software layer that sits between distributed systems and allows them to communicate. It aims to solve problems associated with distributed systems such as heterogeneity and distribution. The Common Object Request Broker Architecture (CORBA) and Java Remote Method Invocation (RMI) are two examples of middleware architectures. These architectures were designed for distributed systems operating on wired networks and when deployed on a wireless network can encounter several problems, such as frequent loss of network connectivity, which can seriously affect their operation.

The Architecture for Location Independent Environments (ALICE) is an architecture developed by the DSG research group in Trinity Collge Dublin that allows mobility support to be added to any object oriented middleware framework that satisfies a minimal set of requirements. This dissertation presents an instantiation of ALICE for the Simple Object Access Protocol (SOAP). SOAP is a lightweight communications protocol based on XML. SOAP will be used as the remote invocation protocol and will be combined with Java to provide an implementation of the abstract components that make up the ALICE Swizzling and Disconnected Operation Layers.
Keywords: Computer Science